Long‐Distance Axonal Growth and Protracted Functional Maturation of Neurons Derived from Human Induced Pluripotent Stem Cells After Intracerebral Transplantation. (15th February 2017) - Niclis, Jonathan C.; Turner, Christopher; Durnall, Jennifer; McDougal, Stuart; Kauhausen, Jessica A.; Leaw, Bryan; Dottori, Mirella; Parish, Clare L.; Thompson, Lachlan H.
Abstract: The capacity for induced pluripotent stem (iPS) cells to be differentiated into a wide range of neural cell types makes them an attractive donor source for autologous neural transplantation therapies aimed at brain repair. Translation to the in vivo setting has been difficult, however, with mixed results in a wide variety of preclinical models of brain injury and limited information on the basic in vivo properties of neural grafts generated from human iPS cells. Here we have generated a human iPS cell line constitutively expressing green fluorescent protein as a basis to identify and characterize grafts resulting from transplantation of neural progenitors into the adult rat brain. The results show that the grafts contain a mix of neural cell types, at various stages of differentiation, including neurons that establish extensive patterns of axonal growth and progressively develop functional properties over the course of 1 year after implantation. These findings form an important basis for the design and interpretation of preclinical studies using human stem cells for functional circuit re‐construction in animal models of brain injury. Stem Cells Translational Medicine 2017;6:1547–1556